2018
DOI: 10.1111/jfd.12782
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge of nocardiosis in teleost fish

Abstract: Nocardia sp. is the causative agent of nocardiosis, a lethal granulomatous disease of the skin, muscle, and various inner tissues affecting various teleost and shellfish. Four species of Nocardia have been isolated from diseased fish and shellfish, namely Nocardia asteroides, Nocardia seriolae, Nocardia salmonicida and Nocardia crassostreae. Therefore, in fish aquaculture, nocardiosis has caused severe economic losses, especially in the Asian region. Considerable research has been performed, since the first re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 44 publications
1
52
0
3
Order By: Relevance
“…Nocardiosis in fish is a systemic chronic nodular disease, and fish infected with this disease showed anorexia, emaciation, haemorrhage, ascites, skin ulcer, oral and abdominal distension with scattered granulomas (Kariya et al., ; Lee et al., ; Maekawa, Yoshida, Wang, & Chen, ). In this study, similar signs were observed in Japanese eels, Anguilla japonica , such as marked ulceration, haemorrhage, weakness and decreased appetite.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nocardiosis in fish is a systemic chronic nodular disease, and fish infected with this disease showed anorexia, emaciation, haemorrhage, ascites, skin ulcer, oral and abdominal distension with scattered granulomas (Kariya et al., ; Lee et al., ; Maekawa, Yoshida, Wang, & Chen, ). In this study, similar signs were observed in Japanese eels, Anguilla japonica , such as marked ulceration, haemorrhage, weakness and decreased appetite.…”
mentioning
confidence: 99%
“…The infection route of Nocardia sp . remains unclear, but occurs plausibly through the gills, muscles and injury sites (Maekawa et al., ). N. seriolae was found to migrate along the blood vessels in eel and induced an immune response by the internal organs.…”
mentioning
confidence: 99%
“…Nocardia seriolae is an opportunistic pathogen, infecting immunocompromised fish through feeds, gills and wounds, which results in a chronic systemic granulomatous disease (Wang et al, ). The clinical signs of infected fish include skin ulcers and numerous white nodular structures on the gills and in the head kidney, trunk kidney, spleen and liver (Maekawa, Yoshida, Wang, & Chen, ). Nocardia seriolae infections have been documented in more than 39 kinds of fishes, both freshwater and especially marine species, such as golden pompano ( Trachinotus ovatus ), snubnose pompano ( T. blochii ), yellow croaker ( Larimichthys crocea ), northern snakehead ( Channa argus ), blotched snakehead ( C. maculata ), largemouth bass ( Micropterus salmoides ), yellow tail ( Seriolae quinqueridiata ), amberjack ( S. dumerelli ) and sea bass ( Lateolabrax japonicas ) (Ho et al, ; Wang, Yi‐Jun, & Jin, ; Wang, Yuan, & Jin, ).…”
Section: Introductionmentioning
confidence: 99%
“…seriolae is an opportunistic pathogen, infecting the immunocompromised fish through feeds, gills and wounds, and causes nodular disease (Manrique et al, ). The clinical sign of infected fish includes skin ulcers, numerous white nodular structures on the gills and in the head kidney, trunk kidney, spleen and liver (Maekawa, Yoshida, Wang, & Chen, ). It was reported that N. seriolae can infect over 20 kinds of freshwater and marine fish, such as yellowtail ( Seriola quinqueradiata ), amberjack ( S. dumerili ), golden pompano ( Trachinotus ovatus ), snubnose pompano ( T. blochii ), large yellow croaker ( Larimichthys crocea ), blotched snakehead ( Channa maculata ) and largemouth bass ( Micropterus salmoides ) (Shimahara et al, ; Wang et al, ; Xia et al, ).…”
Section: Introductionmentioning
confidence: 99%